Infographic on revolutionizing farming: Socio-technical innovation bundling and its impact on farmer empowerment, resilience, and food security in Kenya - Ouya, Fredrick; Lutomia, Cosmas; Nchanji, Eileen; Waswa, Boaz; Ooro, Patrick; Muriithi, Catherine; Njiru, Emerita; Ingasia, Oscar; Otieno, Arnold; Okutoyi, Getrude (2024)
Infographic have been developed from the baseline data on how Socio-Technical Innovation Bundling Impact men and women Farmer's Empowerment, Resilience, and Food Security in Kenya